Solid electrolytic capacitor and manufacturing method

By using a conductive polymer and polyol in the solid electrolyte layer with a specific weight ratio and dielectric film thickness, the solid electrolytic capacitor achieves high withstand voltage and capacitance while maintaining low ESR, overcoming the challenges faced by existing technologies.

JP2025050430APending Publication Date: 2025-04-04NIPPON CHEMI CON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023159225
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Solid electrolytic capacitors face challenges in achieving high withstand voltage while maintaining high capacitance, as increasing the dielectric film thickness to enhance withstand voltage leads to a reduction in electrostatic capacitance.

Method used

The solid electrolytic capacitor incorporates a conductive polymer and a polyol in the solid electrolyte layer, with a weight ratio of conductive polymer to polyol within the range of 1:30 to 1:70, and a dielectric film thickness of 330 nm or more, to achieve high withstand voltage and capacitance.

Benefits of technology

This configuration results in a solid electrolytic capacitor with improved withstand voltage and capacitance, while maintaining low equivalent series resistance (ESR), effectively addressing the limitations of existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025050430000001_ABST
    Figure 2025050430000001_ABST
Patent Text Reader

Abstract

To provide a solid electrolytic capacitor of high voltage resistance and high electrostatic capacitance and a manufacturing method thereof.SOLUTION: A solid electrolytic capacitor comprises an anode body including a dielectric coating, a cathode body opposed to the anode body, and a solid electrolyte layer interposed between the anode body and the cathode body. The solid electrolyte layer contains a conductive polymer (A) and polyol (B). A weight ratio of the conductive polymer (A) and the polyol (B) is A:B=1:30 to 1:70. A manufacturing method of the solid electrolytic capacitor includes a step of forming the solid electrolyte later using a conductive polymer liquid in which conductive polymer particles are dispersed between the anode body including the dielectric coating and the cathode body. In the conductive polymer liquid, the weight ratio of the conductive polymer (A) and the polyol (B) is A:B=1:30 to 1:70.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolytic capacitor and a manufacturing method thereof. [Background technology]

[0002] Capacitors are used in various applications. For example, in the field of power electronics, a power supply circuit converts the power of an AC power source into DC power using a converter circuit, and then converts the DC power into a desired AC power using an inverter circuit. In order to suppress and smooth the pulsation of the DC output from the converter circuit before inputting it to the inverter circuit, a smoothing capacitor is provided. In addition, a decoupling capacitor is provided near a semiconductor switching element such as gallium nitride to ensure stable operation of the semiconductor switching element and to remove noise.

[0003] With the trend toward higher power in recent years, there is a growing demand for capacitors with higher capacitance. Electrolytic capacitors can be made to have a higher capacitance more easily than film capacitors, and can easily meet this demand. Electrolytic capacitors are equipped with valve metals such as tantalum or aluminum as anode and cathode foils. The anode foil is enlarged by forming the valve metal into a sintered body or etched foil, and the enlarged surface has a dielectric film formed by a process such as anodization. An electrolyte is interposed between the anode foil and the cathode foil.

[0004] Electrolytic capacitors can increase the specific surface area by expanding the surface area of ​​the anode foil, and therefore have a large electrostatic capacitance, which can meet the demand for higher capacity. Among electrolytic capacitors, solid electrolytic capacitors using solid electrolytes have attracted attention. Solid electrolytic capacitors are small and have a large capacity, and the high conductivity of the solid electrolyte results in a low equivalent series resistance.

[0005] Known examples of solid electrolytes include manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes. In recent years, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which has a slow reaction rate and excellent adhesion to dielectric films, have rapidly become popular as solid electrolytes. Conductive polymers use acid compounds such as polyanions as dopants, and have a partial structure within the monomer molecule that acts as a dopant, resulting in high conductivity. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-38010 A Summary of the Invention [Problem to be solved by the invention]

[0007] In some fields, such as power electronics, capacitors with high withstand voltages are expected. For example, motor drive inverters installed in electric vehicles require smoothing capacitors with high withstand voltages of 300V or more. Electrolytic capacitors that use electrolyte have a high withstand voltage due to the electrolyte's ability to repair defects in the dielectric film, but they have high ESR in the high frequency range, making it difficult to meet the requirements.

[0008] On the other hand, solid electrolytic capacitors can reduce ESR in the high frequency range compared to electrolytic capacitors that use electrolyte. However, it is difficult to achieve a high withstand voltage from the standpoint of adhesion to the anode foil and the defect repair function of the dielectric film. Moreover, in order to increase the withstand voltage of the capacitor, the thickness of the dielectric film must be increased. As a result, solid electrolytic capacitors aiming for high withstand voltage also significantly reduce the electrostatic capacitance, which is an advantage of solid electrolytic capacitors.

[0009] The present invention has been proposed to solve the above problems, and an object of the present invention is to provide a solid electrolytic capacitor with high withstand voltage and high capacitance, and a method for manufacturing the same. [Means for solving the problem]

[0010] In order to solve the above problems, the solid electrolytic capacitor of the present embodiment includes an anode body having a dielectric film, a cathode body facing the anode body, and a solid electrolyte layer interposed between the anode body and the cathode body, the solid electrolyte layer containing a conductive polymer and a polyol, and a weight ratio of the conductive polymer (A) to the polyol (B) is within a range of A:B=1:30 to 1:70.

[0011] The dielectric coating of the anode body may be a chemical conversion coating having a withstand voltage of 300V or more.

[0012] The dielectric coating of the anode body may have a thickness of 330 nm or more.

[0013] The polyol may be glycerin.

[0014] The weight ratio of the conductive polymer (A) to the glycerin (B) may be within the range of A:B=1:40 to 1:70.

[0015] A separator that holds the solid electrolyte layer may be interposed between the anode body and the cathode body, and the separator may be made of fibrillated cellulose.

[0016] The electrolyte may not be contained.

[0017] In order to solve the above problems, a method for producing a solid electrolytic capacitor according to the present embodiment includes a step of forming a solid electrolyte layer between an anode body having a dielectric film and the cathode body using a conductive polymer solution in which conductive polymer particles are dispersed, the conductive polymer solution including a conductive polymer and a polyol, and a weight ratio of the conductive polymer (A) to the polyol (B) is within a range of A:B=1:30 to 1:70.

[0018] The dielectric coating of the anode body may be a chemical conversion coating having a withstand voltage of 300V or more.

[0019] The dielectric coating of the anode body may have a thickness of 330 nm or more.

[0020] The polyol may be glycerin, and the weight ratio of the conductive polymer (A) to the glycerin (B) may be within the range of A:B=1:40 to 1:70. Effect of the Invention

[0021] According to the present invention, the solid electrolytic capacitor has a high withstand voltage and a high capacity. [Brief description of the drawings]

[0022] [Figure 1] This is a graph showing the relationship between the amount of remaining solvent and the withstand voltage for each type of polyol in a solid electrolytic capacitor when a voltage of 650 Vfs is applied during formation. [Diagram 2] This is a graph showing the relationship between the amount of remaining solvent and the capacitance for each type of polyol in a solid electrolytic capacitor when a voltage of 650 Vfs is applied during formation. [Diagram 3] 1 is a graph showing the relationship between the amount of remaining solvent and the withstand voltage for a solid electrolytic capacitor when an applied voltage of 300 Vfs during formation is used for each type of polyol. [Figure 4] 1 is a graph showing the relationship between the amount of remaining solvent and the capacitance for each type of polyol in a solid electrolytic capacitor when a voltage of 300 Vfs is applied during formation. [Diagram 5]This is a graph showing the relationship between the amount of remaining solvent and ESR for each type of polyol in a solid electrolytic capacitor when the voltage applied during formation is 650Vfs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, a solid electrolytic capacitor according to an embodiment will be described, however, the present invention is not limited to the embodiment described below.

[0024] (Solid electrolytic capacitor) A solid electrolytic capacitor is a passive element that obtains capacitance by the dielectric polarization action of a dielectric film and stores and discharges electric charge. This solid electrolytic capacitor includes a capacitor element. The capacitor element includes an anode body, a cathode body, and a solid electrolyte layer, and does not contain an electrolytic solution. A dielectric film is formed on the surface of the anode body. The anode body and the cathode body face each other with the solid electrolyte layer between them. The solid electrolyte layer is interposed between the dielectric film of the anode body and the cathode body, and functions as a true cathode in close contact with the dielectric film of the anode body.

[0025] A separator may be interposed between the anode body and the cathode body. The separator holds the solid electrolyte layer. The separator also prevents shorting between the anode body and the cathode body. If the solid electrolyte layer can retain its shape by itself and separates the anode body and the cathode body, the separator can be omitted from the configuration of the solid electrolytic capacitor.

[0026] This solid electrolytic capacitor is classified into, for example, a laminated type, a wound type, and a flat type. In the laminated type, anode bodies and cathode bodies are alternately laminated with a separator sandwiched between them. In the wound type, the anode bodies and cathode bodies are wound with a separator sandwiched between them. In the flat type, a solid electrolyte layer and a cathode body are laminated on an anode body.

[0027] (electrode body) The anode body and the cathode body are foil bodies made of a valve metal. The foil body may be formed by stretching the valve metal or the like, or may be formed by sintering a powder of the valve metal. The valve metal may be aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, or the like. The purity of the valve metal is preferably 99.9% or more for the anode body and 99% or more for the anode body, and may contain silicon, iron, copper, magnesium, zinc, or the like.

[0028] In a wound-type electrolytic capacitor, the anode body is a long strip-shaped anode foil, while in a laminated-type and flat-type electrolytic capacitor, the anode body is a flat anode foil. A surface-expanding layer is formed on one or both sides of the anode body. The surface-expanding layer is an etching layer formed by etching the foil body, a sintered layer formed by sintering valve metal powder, or a deposition layer formed by depositing valve metal particles on the foil. That is, the surface-expanding layer has a porous structure and is composed of tunnel-shaped pits, spongy pits, or voids between densely packed powder or particles.

[0029] The dielectric film is formed on one or both sides of the anode body on which the surface-expanding layer is formed. When the surface-expanding layer is formed, the dielectric film is formed on the surface layer of the surface-expanding layer along the unevenness of the surface-expanding layer. The dielectric film is typically an oxide film formed on the surface layer of the anode body, and if the anode body is made of aluminum, it is an aluminum oxide layer obtained by oxidizing the surface of the surface-expanding layer. In the chemical conversion treatment for forming the dielectric film, a voltage is applied to the anode body in a chemical conversion solution so as to achieve a desired withstand voltage. The chemical conversion solution is a solution that does not contain halogen ions, and is, for example, a phosphoric acid-based chemical conversion solution such as ammonium dihydrogen phosphate, a boric acid-based chemical conversion solution such as ammonium borate, or an adipic acid-based chemical conversion solution such as ammonium adipate.

[0030] In this solid electrolytic capacitor, the dielectric film has a thickness of 330 nm or more. A dielectric film having a thickness of 330 nm or more exhibits a withstand voltage of 300 V or more. The value of 300 V is a value that takes into account tolerances in order to set the product rated withstand voltage to at least 250 V.

[0031] In the case of a wound-type electrolytic capacitor, the cathode body is preferably a cathode foil made of a valve metal and stretched. The cathode body has a surface expansion layer formed thereon, as in the anode body. A plain foil without a surface expansion layer may be used as the cathode body. The cathode body may have a natural oxide film or a thin oxide film of about 1 to 10 Vfs formed by chemical conversion treatment. The natural oxide film is formed by the reaction of the cathode body with oxygen in the air.

[0032] The cathode body may further include a conductive layer. The conductive layer may mainly contain an inorganic substance or an inorganic compound. Examples of the inorganic substance or inorganic compound include titanium, zirconium, tantalum, niobium, nitrides or carbides thereof, aluminum carbide, carbon materials, and composites or mixtures thereof.

[0033] In the case of a laminated electrolytic capacitor, the cathode body is preferably a laminate of a metal layer and a carbon layer. The carbon layer of the cathode body is arranged facing the anode body. The carbon layer is formed in a paste form, and is then coated on the electrolyte layer after the electrolyte layer is formed on the anode body, and is then hardened by heating. The metal layer is, for example, a silver layer, and is formed in a paste form, and is then coated on the carbon layer, and is then hardened by heating.

[0034] (Solid electrolyte layer) The solid electrolyte layer is a layer containing a conductive polymer. The conductive polymer is a self-doped conjugated polymer doped with an intramolecular dopant, or a conjugated polymer doped with an external dopant molecule. The conjugated polymer is obtained by chemically oxidizing or electrolytically oxidizing a monomer having a π-conjugated double bond or a derivative thereof. The dopant or the external dopant molecule is an acceptor that easily accepts electrons into the conjugated polymer, or a donor that easily gives electrons to the conjugated polymer, and this allows the conductive polymer to exhibit high conductivity.

[0035] The conjugated polymer may be any known polymer without any particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. These conjugated polymers may be used alone, or in combination of two or more kinds, or may be a copolymer of two or more kinds of monomers.

[0036] Among the above conjugated polymers, preferred are conjugated polymers obtained by polymerizing thiophene or its derivatives, and preferred are conjugated polymers obtained by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxine), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or derivatives thereof. As the thiophene derivative, a compound selected from thiophenes having substituents at the 3rd and 4th positions is preferred, and the substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the carbons at the 3rd and 4th positions. The number of carbon atoms of the alkyl group or alkoxy group is preferably 1 to 16.

[0037] In particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, that is, poly(3,4-ethylenedioxythiophene) called PEDOT, is preferred. A substituent may be added to 3,4-ethylenedioxythiophene. For example, an alkylated ethylenedioxythiophene having an alkyl group having 1 to 5 carbon atoms added as a substituent may be used. Examples of alkylated ethylenedioxythiophene include methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), butylated ethylenedioxythiophene (i.e., 2-butyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), and 2-alkyl-3,4-ethylenedioxythiophene.

[0038] The dopant may be any known dopant without any particular limitation. The dopant may be used alone or in combination of two or more. A polymer or monomer may also be used. For example, the dopant may be an inorganic acid such as a polyanion, boric acid, nitric acid, or phosphoric acid, or an organic acid such as acetic acid, oxalic acid, citric acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalate borate acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, or butylnaphthalenesulfonic acid.

[0039] Examples of the polyanion include substituted or unsubstituted polyalkylene, substituted or unsubstituted polyalkenylene, substituted or unsubstituted polyimide, substituted or unsubstituted polyamide, and substituted or unsubstituted polyester, and include polymers consisting of only structural units having an anionic group, and polymers consisting of structural units having an anionic group and structural units not having an anionic group.Specific examples of the polyanion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylic acid, and polymaleic acid.

[0040] An example of the conductive polymer is poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonic acid, and hereinafter this conductive polymer is referred to as PEDOT:PSS.

[0041] This solid electrolyte layer can be formed using a conductive polymer liquid. The conductive polymer liquid is a dispersion or solution in which a conductive polymer is dispersed or dissolved. In the solid electrolyte layer forming step, the anode body and the cathode body, or a wound body in which a separator is added to these, is immersed in the conductive polymer liquid. Alternatively, in the solid electrolyte layer forming step, the anode body is coated with the conductive polymer liquid. The conductive polymer liquid may be immersed or coated once or multiple times. The wound body may be placed in a reduced pressure environment to be impregnated with the conductive polymer liquid.

[0042] The solid electrolyte layer contains a polyol together with the conductive polymer. The polyol may be one or more selected from ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, glycerin, and polyglycerin. When the solid electrolyte layer is formed using a conductive polymer liquid, the polyol is included in the conductive polymer liquid. The polyol may be a dispersion or solution of the conductive polymer liquid, or may be added to the conductive polymer liquid as an additive.

[0043] The polyol contained in the conductive polymer liquid adheres to the wound body or the anode body together with the conductive polymer when the wound body or the anode body is impregnated with or coated with the conductive polymer liquid. The weight ratio of the conductive polymer (A) to the polyol (B) is within the range of A:B=1:30 to 1:70.

[0044] In general, when a liquid other than polyol is included in the solid electrolyte layer, the capacitance of the solid electrolytic capacitor decreases. The mode changes when the weight ratio of the conductive polymer (A) and the liquid other than polyol (C) is A:C = 1:30. Therefore, when a liquid other than polyol is included in the solid electrolyte layer and A:C = 1:30, the withstand voltage drops compared to when A:C is less than 1:30.

[0045] On the other hand, when a conductive polymer and a polyol are combined, the solid electrolytic capacitor exhibits a high capacitance. Furthermore, the weight ratio of the conductive polymer (A) to the polyol (B) is within the range of A:B=1:30 to 1:70. When the weight ratio is within the range of A:B=1:30 to 1:70, the capacitance of the solid electrolytic capacitor is further improved. Moreover, when polyol is included in the solid electrolyte layer, the weight ratio of the conductive polymer (A) to the polyol (B) within the range of A:B=1:30 to 1:70 further improves the withstand voltage of the solid electrolytic capacitor, unlike liquids other than polyol.

[0046] Preferably, the polyol is glycerin, and the weight ratio of the conductive polymer (A) to the glycerin (D) is within the range of A:D=1:40 to 1:70. When a polyol is added to the conductive polymer solution, if the concentration of the conductive polymer is 1 wt%, the weight ratio of the conductive polymer (A) to the polyol (B) can be theoretically within the range of A:B=1:99. However, when the polyol is other than glycerin, if the weight ratio of the conductive polymer (A) to the polyol (B) is A:B=1:30 or more, the equivalent series resistance (ESR) of the solid electrolytic capacitor will rise sharply compared to when it is below this range.

[0047] On the other hand, when the polyol is glycerin, the ESR of the solid electrolytic capacitor remains almost unchanged even if the weight ratio of the conductive polymer (A) to the glycerin (D) is A:D = 1:40 or more. Therefore, when the polyol is glycerin and the weight ratio of the conductive polymer (A) to the glycerin (D) is within the range of A:D = 1:40 to 1:70, the withstand voltage of the solid electrolytic capacitor is further increased while achieving both high capacitance and low ESR.

[0048] The conductive polymer liquid may contain a dispersion medium or solvent, a pH adjuster, and an additive, in addition to the conductive polymer and polyol. The dispersion medium or solvent may be any one that disperses or dissolves the conductive polymer particles or powder. The pH adjuster improves the acidity of the conductive polymer liquid so that the anode body, cathode body, and separator do not dissolve. Examples of additives include organic binders, surfactants, dispersants, antifoaming agents, coupling agents, antioxidants, and ultraviolet absorbers.

[0049] The dispersion medium or solvent of the conductive polymer liquid is water or a mixture of water and an organic solvent. Suitable examples of the organic solvent include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, and nitrile compounds. The mixing ratio of the dispersion medium or solvent and the polyol is not particularly limited as long as the conductive polymer can be dispersed or dissolved and the weight ratio of the conductive polymer (A) to the polyol (B) is within the range of A:B=1:30 to 1:70.

[0050] Examples of polar solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. Examples of alcohols include methanol, ethanol, propanol, and butanol. Examples of esters include ethyl acetate, propyl acetate, and butyl acetate. Examples of hydrocarbons include hexane, heptane, benzene, toluene, and xylene. Examples of carbonate compounds include ethylene carbonate and propylene carbonate. Examples of ether compounds include dioxane and diethyl ether. Examples of chain ethers include ethylene glycol dialkyl ether, propylene glycol dialkyl ether, polyethylene glycol dialkyl ether, and polypropylene glycol dialkyl ether. Examples of heterocyclic compounds include 3-methyl-2-oxazolidinone. Examples of nitrile compounds include acetonitrile, glutarodinitrile, methoxyacetonitrile, propionitrile, and benzonitrile.

[0051] The polyol may be contained in the conductive polymer liquid or may be impregnated into the solid electrolyte layer by a known method, for example, by dripping the polyol onto the capacitor element on which the solid electrolyte layer is formed, or by dripping or spraying the polyol onto the solid electrolyte layer.

[0052] (Separator) The separator may be made of cellulose such as kraft, Manila hemp, esparto, hemp, rayon, or the like, or mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins; and the like, and these resins may be used alone or in combination.

[0053] The separator may be fibrillated by generating thin fibers that branch out from the surface of the original fibers, such as fibrillated cellulose. Fibrillated cellulose can be formed, for example, by beating. The fibrillated fibers are entangled with each other using the fibrillated thin fibers, improving the strength of the separator. This allows the separator to be made thinner.

[0054] In addition, the electronic paths formed by the conductive polymers along the thin fibers branching off from the surface of the original fibers become physically thin. It is estimated that many of these thin electronic paths exist within a separator made of fibrillated cellulose. When a large current flows through a thin electronic path through defects in the dielectric film, the thin electronic path becomes more likely to be blocked, and short circuits are suppressed. In other words, this is expected to improve the voltage resistance of solid electrolytic capacitors. The blocking of the electronic path here is achieved by insulating the conductive polymer due to Joule heat generated by the flow of current.

[0055] Furthermore, in a system that combines a fibrillated cellulose separator with a conductive polymer and a polyol, it is presumed that the polyol penetrates into the fibrillated cellulose fibers, causing the fibers to expand. This is because the hydroxyl groups of the polyol have a high affinity for cellulose. If this happens, the electron paths carried by the conductive polymer will be subdivided, and it is expected that the withstand voltage will be further improved. EXAMPLES

[0056] The solid electrolytic capacitors of the examples will be described in more detail below, but the present invention is not limited to the examples described below.

[0057] (Examples 1-17) Solid electrolytic capacitors of Examples 1 to 17 and Comparative Examples 1 to 11 were produced. The common anode body and cathode body were used in Examples 1 to 17 and Comparative Examples 1 to 11. The anode body was an aluminum anode foil, and the cathode body was an aluminum cathode foil. The anode foil was etched to form a surface-expanding layer consisting of tunnel-shaped etching pits. The anode foil was then chemically treated to form a dielectric film having a thickness of 715 nm. During the chemical treatment, the anode foil was immersed in an aqueous solution of ammonium borate at a liquid temperature of 85°C, and a voltage was applied until the voltage reached 650 V while a constant current of 2 mA was applied. The cathode foil was a plain foil that had not been subjected to surface expansion or chemical treatment.

[0058] The anode foil and the cathode foil were wound together with a separator between them to prepare a wound body. The separator was fibrillated cellulose or manila paper depending on the example and comparative example.

[0059] The wound body was impregnated with a conductive polymer liquid, so that conductive polymer particles were attached to the dielectric film of the anode foil, the cathode foil, and the inside of the separator. PEDOT:PSS particles were dispersed in the conductive polymer liquid. The dispersion medium was water. A conductive polymer liquid with a conductive polymer concentration of 3.3 wt% was prepared. Various amounts of polyol or sulfolane were added to this conductive polymer liquid, and ultrasonic dispersion treatment was performed for 20 minutes. The conductive polymer liquid was impregnated in an environment with a reduced pressure of 10 kPa for 3 minutes. After being impregnated with the conductive polymer liquid, the wound body was dried in a temperature environment of 60°C for 10 minutes, and further dried at 120°C or 150°C.

[0060] This produced a capacitor element with a solid electrolyte layer formed between the anode foil and the cathode foil. The capacitor element had a diameter of 10 mm and a height of 12.5 mm. This capacitor element was then subjected to a restoration chemical formation. In the restoration chemical formation, the capacitor element was immersed in a boric acid aqueous solution at a liquid temperature of 85°C, and a voltage was applied until it reached 650 V while passing a constant current of 2 mA, and the voltage was held for 20 minutes. The boric acid aqueous solution was then washed away from the wound body with pure water, and the wound body was dried in a temperature environment of 105°C.

[0061] The capacitor element was housed in an aluminum case with one end closed and the other end open. A rubber seal was inserted into the opening of the aluminum case, and the outside of the aluminum case was crimped to seal the capacitor element. Thus, the production of the solid electrolytic capacitors of Examples 1 to 17 and Comparative Examples 1 to 11 was completed.

[0062] (Characteristics test contents) The residual amount of solvent, withstand voltage, and capacitance of the solid electrolytic capacitors of Examples 1 to 17 and Comparative Examples 1 to 11 were measured. Since water was completely evaporated by drying, the residual amount of solvent is the remaining amount of polyol or sulfolane. This residual amount of solvent is the weight ratio of the remaining solvent when the PEDOT:PSS in the solid electrolytic capacitor is set to 1.

[0063] The weight of PEDOT:PSS in the solid electrolytic capacitor was calculated from the difference in weight of the capacitor element before and after impregnation with the conductive polymer liquid, and the concentration of the conductive polymer. The remaining amount of solvent was calculated from the weight of the capacitor element before impregnation with the conductive polymer liquid, the weight of the capacitor element after drying, and the weight of PEDOT:PSS in the solid electrolytic capacitor. After measuring the remaining amount of solvent, the capacitor element was placed in an aluminum case and sealed with a rubber seal.

[0064] The capacitance was measured using an LCR meter (Agilent ZM2376, manufactured by NF Corporation). The ambient temperature during the measurement was 25°C, the DC bias was 1.5V, the AC current level was a sine wave of 1.0Vrms, and the measurement frequency was 120Hz. The solid electrolytic capacitor was left at an ambient temperature of 105°C for 5 minutes, and then the withstand voltage was measured. The ambient temperature during the withstand voltage measurement was 105°C, and the voltage was increased from 200V at intervals of 1V every 10 seconds. The current-voltage rise curve was examined, and the voltage (V) at which scintillation was observed on the current rise curve was taken as the withstand voltage. A power supply (HV-X series, manufactured by Takasago Manufacturing Co., Ltd.) and a recording device (PC-7000, manufactured by Sanwa Electric Instruments Co., Ltd.) were used to measure the withstand voltage.

[0065] (Characteristics test results) Tables 1 to 4 below show the separator type, the type of solvent other than water in the conductive polymer solution and the remaining amount of solvent, as well as the measurement results of capacitance and withstand voltage. (Table 1) TIFF2025050430000002.tif82161

[0066] (Table 2) TIFF2025050430000003.tif101161

[0067] (Table 3) TIFF2025050430000004.tif71161

[0068] (Table 4) TIFF2025050430000005.tif71161

[0069] Moreover, Examples 1 to 10, Examples 12 to 17, Comparative Examples 1 to 4, and Comparative Examples 6 to 11 in Tables 1 to 4 above were grouped into series according to the amount of remaining solvent, and graphs were created for each series. Fig. 1 is a graph showing the relationship between the amount of remaining solvent and the withstand voltage. Fig. 2 is a graph showing the relationship between the amount of remaining solvent and the electrostatic capacitance. In Figs. 1 and 2, the series of plots with triangle marks is ethylene glycol, the series of plots with circle marks is glycerin, the series of plots with asterisk marks is butanediol, the series of plots with x marks is diethylene glycol, and the series of plots with diamond marks is sulfolane.

[0070] As shown in Tables 1 to 4, the polyol added to the conductive polymer liquids of Examples 1 to 17 and Comparative Examples 1 to 5 was ethylene glycol, glycerin, butanediol, or diethylene glycol. Sulfolane was added to the conductive polymer liquids of Comparative Examples 6 to 11.

[0071] The solid electrolyte layers of Comparative Examples 1 and 2 and Examples 1 to 5 contain ethylene glycol, but the residual solvent amount of ethylene glycol is adjusted to differ by 10 to 70 times. The solid electrolyte layers of Comparative Examples 3 and 4 and Examples 6 to 10 contain glycerin, but the residual solvent amount of glycerin is adjusted to differ by 10 to 70 times. The solid electrolyte layers of Comparative Examples 6 to 11 contain sulfolane, but the residual solvent amount of sulfolane is adjusted to differ by 10 to 70 times.

[0072] Each of the Examples and Comparative Examples includes fibrillated cellulose as a separator, except for Comparative Example 5 and Example 11. Comparative Example 5 and Example 11 include manila paper as a separator.

[0073] 1, when comparing the Example in which the solvent other than water in the conductive polymer liquid is polyol with the Comparative Example in which the solvent other than water in the conductive polymer liquid is sulfolane, there is no significant difference in the withstand voltage between the two when the remaining amount of solvent is up to 20 times. However, when the solvent other than water in the conductive polymer liquid is sulfolane, the withstand voltage drops sharply when the remaining amount of solvent becomes 30 times.

[0074] On the other hand, when the solvent other than water in the conductive polymer liquid is polyol, the withstand voltage continues to improve in proportion to the increase in the remaining amount of solvent, even if the remaining amount of solvent is 30 times or more. When the solvent other than water in the conductive polymer liquid is sulfolane, there is a tendency for the withstand voltage to improve in proportion to the increase in the remaining amount of solvent when the remaining amount of solvent is 40 times or more. However, when the solvent other than water in the conductive polymer liquid is polyol, the withstand voltage improves in proportion to the remaining amount of solvent, and there is a noticeable difference in the withstand voltage when the solvent other than water in the conductive polymer liquid is polyol and the remaining amount of solvent is 30 times or more.

[0075] Moreover, as shown in Tables 1 to 4 above and Figure 2, when comparing the Examples in which the solvent other than water in the conductive polymer solution is polyol with the Comparative Example in which sulfolane is used, there is a large difference in capacitance between the two over the entire range. The Examples in which the solvent other than water in the conductive polymer solution is polyol have good capacitance of the solid electrolytic capacitor.

[0076] In this way, it was confirmed that when the remaining amount of solvent is 30 times or more, i.e., when the weight ratio of the conductive polymer (A) to the polyol (B) is A:B=1:30 or more, the voltage resistance of the solid electrolytic capacitor is improved and the capacitance is further increased, unlike other solvents such as sulfolane.

[0077] Furthermore, as shown in Table 2 above, except for the different separators, Comparative Example 4 corresponds to Comparative Example 5, and Example 8 corresponds to Example 11. The separators in Comparative Example 4 and Example 8 are fibrillated cellulose, and the separators in Comparative Example 5 and Example 11 are manila paper. As can be seen from the comparison between Comparative Example 4 and Comparative Example 5, and between Example 8 and Example 11, it was confirmed that when the solid electrolyte layer contains a conductive polymer and a polyol, and the separator is fibrillated cellulose, the withstand voltage of the solid electrolytic capacitor is further improved.

[0078] (Examples 18-23) The solid electrolytic capacitors of Examples 18 to 23 and Comparative Examples 12 to 14 were produced. The solid electrolytic capacitors of Examples 18 to 23 and Comparative Examples 12 to 14 differ from the other Examples in that the thickness of the dielectric film of the anode body was 330 nm. The anode foil was immersed in an aqueous solution of ammonium borate at a liquid temperature of 85° C., and a voltage was applied until the voltage reached 300 V while a constant current of 2 mA was applied. The other configurations of the solid electrolytic capacitors of Examples 18 to 23 and Comparative Examples 12 to 14 were the same as those of Examples 1 to 17, and the solid electrolytic capacitors of Examples 18 to 23 were produced by the same manufacturing method and under the same conditions as those of Examples 1 to 17.

[0079] The separators in Examples 18 to 23 and Comparative Examples 12 to 14 are all fibrillated cellulose. The polyol in Examples 18 to 23 is ethylene glycol or glycerin, and sulfolane is added to the solid electrolyte layers in Comparative Examples 12 to 14.

[0080] (Characteristics test contents) The remaining amount of solvent, the withstand voltage, and the electrostatic capacitance were measured for the solid electrolytic capacitors of Examples 18 to 23 and Comparative Examples 12 to 14. The remaining amount of solvent, the withstand voltage, and the electrostatic capacitance were measured by the same method and under the same conditions as in Examples 1 to 17.

[0081] (Characteristics test results) Table 5 below shows the separator type, the type of solvent other than water in the conductive polymer liquid and the remaining amount of solvent, as well as the measurement results of capacitance and withstand voltage. (Table 5) TIFF2025050430000006.tif101161

[0082] Examples 18 to 23 and Comparative Examples 12 to 14 in Table 5 above were grouped into series according to the amount of remaining solvent, and graphs were created for each series. Fig. 3 is a graph showing the relationship between the amount of remaining solvent and the withstand voltage. Fig. 4 is a graph showing the relationship between the amount of remaining solvent and the electrostatic capacity. In Figs. 3 and 4, the series of plots with triangles is ethylene glycol, the series of plots with circles is glycerin, and the series of plots with diamonds is sulfolane.

[0083] As shown in Table 5 above and Figure 3, when comparing the Example in which the solvent other than water in the conductive polymer solution is polyol with the Comparative Example in which sulfolane is used, there is a difference in the withstand voltage over the entire range, even when the dielectric film is formed with an applied voltage of 300 V. The Example in which the solvent other than water in the conductive polymer solution is polyol has an improved withstand voltage of the solid electrolytic capacitor.

[0084] 4, even when the dielectric film is formed at an applied voltage of 300 V, there is a difference in capacitance over the entire range between the Example in which the solvent other than water in the conductive polymer solution is polyol and the Comparative Example in which sulfolane is used. The Example in which the solvent other than water in the conductive polymer solution is polyol has an improved capacitance of the solid electrolytic capacitor.

[0085] This confirmed that, unlike other solvents such as sulfolane, the voltage resistance of the solid electrolytic capacitor improves and the capacitance is even higher when the weight ratio of the conductive polymer (A) and polyol (B) is A:B=1:30 or more, even when a dielectric film 330 nm or more thick is formed at an applied voltage of 300 V or more. In particular, it was confirmed that when a dielectric film 715 nm or more thick is formed at an applied voltage of 600 V or more, there is a large difference in the voltage resistance and capacitance compared to other solvents such as sulfolane.

[0086] (ESR test) The equivalent series resistance (ESR) of the solid electrolytic capacitors of Comparative Example 2 and Examples 1 to 5 using ethylene glycol, Examples 12 to 14 using butanediol, Examples 15 to 17 using diethylene glycol, and Comparative Example 4 and Examples 6 to 10 using glycerin was measured. The ESR was measured using an LCR meter (Agilent ZM2376, manufactured by NF Corporation). The ambient temperature during the measurement was 25°C, the DC bias was 1.5V, the AC current level was a sine wave of 1.0Vrms, and the measurement frequency was 100kHz.

[0087] The results of this ESR measurement test are shown in Table 6 below. (Table 6) TIFF2025050430000007.tif191136

[0088] Based on Table 6 above, the relationship between the remaining amount of solvent and ESR for each type of polyol is shown in Figure 5. In Figure 5, the series of plots marked with triangles is ethylene glycol, the series of plots marked with circles is glycerin, the series of plots marked with asterisks is butanediol, and the series of plots marked with x is diethylene glycol.

[0089] As shown in Table 6 and Figure 5, ethylene glycol and diethylene glycol keep the ESR of solid electrolytic capacitors low when the weight ratio of conductive polymer (A) to polyol (B) is up to A:B = 1:30. However, when ethylene glycol and diethylene glycol are used, the ESR of the solid electrolytic capacitor increases when the weight ratio of conductive polymer (A) to polyol (B) is A:B = 1:40 or more, and when the weight ratio of conductive polymer (A) to polyol (B) is A:B = 1:50 or more, the ESR of the solid electrolytic capacitor increases sharply. Also, when butanediol is used, the ESR of solid electrolytic capacitors is generally high.

[0090] However, glycerin keeps the ESR of the solid electrolytic capacitor extremely low, even when the weight ratio of the conductive polymer (A) to the glycerin (C) is A:C = 1:40 or more. Moreover, when the polyol is glycerin, as shown in Figure 1, glycerin further improves the withstand voltage of the solid electrolytic capacitor when the weight ratio of the conductive polymer (A) to the glycerin (B) is A:B = 1:40 or more. In addition, the ESR characteristics and withstand voltage characteristics become even better when the weight ratio of the conductive polymer (A) to the glycerin (B) is A:B = 1:50 or more.

[0091] This confirmed that when the polyol is glycerin and the weight ratio of the conductive polymer (A) to the glycerin (B) is A:B=1:40 or more, the solid electrolytic capacitor has a high capacitance, a high withstand voltage, and a low ESR. It was also confirmed that when the polyol is glycerin and the weight ratio of the conductive polymer (A) to the glycerin (B) is A:B=1:50 or more, the solid electrolytic capacitor has a high capacitance, and a particularly high withstand voltage and low ESR.

Claims

1. an anode body having a dielectric coating; A cathode body facing the anode body; a solid electrolyte layer interposed between the anode body and the cathode body; Equipped with the solid electrolyte layer includes a conductive polymer and a polyol, the weight ratio of the conductive polymer (A) to the polyol (B) is within a range of A:B=1:30 to 1:70; A solid electrolytic capacitor characterized by:

2. the dielectric coating of the anode body is a chemical conversion coating having a withstand voltage of 300 V or more; 2. The solid electrolytic capacitor according to claim 1 .

3. The dielectric coating of the anode body has a thickness of 330 nm or more; 2. The solid electrolytic capacitor according to claim 1 .

4. The polyol is glycerin; 4. The solid electrolytic capacitor according to claim 2 or 3.

5. The weight ratio of the conductive polymer (A) to the glycerin (B) is within a range of A:B=1:40 to 1:70; 5. The solid electrolytic capacitor according to claim 4,

6. a separator that holds the solid electrolyte layer is interposed between the anode body and the cathode body, the separator is fibrillated cellulose; 4. The solid electrolytic capacitor according to claim 1, wherein

7. Does not contain electrolyte.

4. The solid electrolytic capacitor according to claim 1, wherein

8. The method includes a step of forming a solid electrolyte layer between an anode body having a dielectric film and the cathode body by using a conductive polymer solution in which conductive polymer particles are dispersed, The conductive polymer liquid contains a conductive polymer and a polyol, the weight ratio of the conductive polymer (A) to the polyol (B) is within a range of A:B=1:30 to 1:70; A method for producing a solid electrolytic capacitor comprising the steps of:

9. the dielectric coating of the anode body is a chemical conversion coating having a withstand voltage of 300 V or more; 9. The method for producing a solid electrolytic capacitor according to claim 8,

10. The dielectric coating of the anode body has a thickness of 330 nm or more; 9. The method for producing a solid electrolytic capacitor according to claim 8,

11. The polyol is glycerin, The weight ratio of the conductive polymer (A) to the glycerin (B) is within a range of A:B=1:40 to 1:70; 11. The method for producing a solid electrolytic capacitor according to claim 8, wherein

Citation Information

Patent Citations

  • Solid electrolytic capacitor and method for manufacturing solid electrolytic capacitor

    JP2017038010A